#TITLE_ALTERNATIVE# - ADIPUTRA (NIM : 12213046), ENRICO
Carbon dioxide flooding has been known for increasing the production of oil by the means of Enhanced Oil Recovery (EOR). Conventional carbon dioxide flood aim for reaching Minimum Miscibility Pressure (MMP) to alter oil property in reservoir. In spite of that, the conditions are, most of fields have reached mature state, which mean the pressure of reservoirs are depleted. Then, it is hard for carbon dioxide to be miscible in oil. Carbonated Water is water into which carbon dioxide has been dissolved under certain condition. Carbonated Water Injection (CWI) technique could be seen as a solution for injecting carbon dioxide bellow MMP. The performance of this new injection technique is presented by physical model made to show wettability alteration mechanism of Carbonated Water. The physical model made by glass chamber filled with unaltered water. Saturated core then placed inside the chamber, bellow a funnel shaped narrow tube that read the oil recovery. The chamber then closed and stream of carbon dioxide flown to water body. Water inside the chamber then altered to be carbonated water after a period of soaking time. The oil expelled from the core spontaneously can be measured by reading the graduation on the top of tube, similar with Amott Cell procedures. The process repeated for several concentrations of carbon dioxide in water. The change of injection pressure, power of hydrogen (pH) and oil recovery are measured respected to time. The value of every cases, including unaltered water saturation case, compared each other. The optimum condition for this technique could be estimated by amount of oil recovered and soaking time period. This injection technique give promising result compared to conventional method, shown by considerably high recovery. This new technique can give encouraging outcome if applied to field, either in full scale or near wellbore stimulation.